Platelet-Rich Plasma-Releasate (PRPr) for the Treatment of Discogenic Low Back Pain Patients: Long-Term Follow-Up Survey - Koji Akeda; Norihiko Takegami; Junichi Yamada; Tatsuhiko Fujiwara; Kohshi Ohishi; Satoshi Tamaru; Akihiro Sudo (Medicina, 2022)
Background and Objectives: Clinical studies of platelet-rich plasma (PRP) for the treatment of low back pain (LBP) have been reported; however, less is known about its long-term efficiency. Materials and Methods: This study was a long-term follow-up of a previous prospective clinical feasibility study for the use of PRP releasate (PRPr) to treat discogenic LBP patients. Among 14 patients, 11 patients were evaluated for a long-term survey. The efficacy was assessed by a visual analogue scale (VAS) for LBP intensity and the Roland-Morris Disability Questionnaire (RDQ) for LBP-related disability. Radiographic disc height was evaluated for seven patients. Results: Improvements in VAS and RDQ were sustained at an average of 5.9 years after the intradiscal injection of PRPr (p < 0.01 vs. baseline, respectively). Clinically meaningful improvements (more than 30% decrease from baseline) in VAS and RDQ were identified in 91% of patients at final survey. The radiographic measurement of disc height of PRPr-injected discs showed a mild decrease (13.8% decrease compared to baseline) during the average 5.9 years. Conclusions: The results of this study with a small number of patients suggest that the intradiscal injection of PRPr has a safe and efficacious effect on LBP improvement for more than 5 years after treatment. Further large-scale studies would be needed to confirm the clinical evidence for the use of PRPr for the treatment of patients with discogenic LBP.